Relationship between the aspects of functional alterations and their impact in the quality of life of people with sequels of Encephalic Vascular Accidents (EVA) - Miriam Cabrera Corvelo Delboni; Patrícia de Camargo e Melo Malengo; Evelyn Paulina Rapp Schmidt Rapp Schmidt (O Mundo da Saúde)
The increase of life expectancy produces a change in the profile of morbity of diseases such as Encephalic Vascular Accident (EVA), causing sequels that influence the Quality of Life of survivors, something which makes necessary to understand and to quantify the impact of that pathology. This work aimed at establishing a correlation between Functional Independence Measurement (FIM) scales and the Stroke Specific Quality of Life Scale (SS-QOL), and was carried out with 15 patients with EVA diagnosis in the Sector of Occupational Therapy of the Clinic School Promove of University Center São Camilo after receiving approval by the Ethics Committee. The scales were applied to 15 hemiplegic patients with an average age of 64.6 years. Data analysis shows a correlation between two domains (work and productivity and self-medication) among the twelve presented by SS-QOL with FIM. The study does not show any correlation between the degree of functional independence and the other domains of Quality of Life of SS-QOL. Other relevant statistical results of this study were: mobility scores in males are significantly higher than those of females; social roles scores are statistically higher among single and divorced patients and widows and widowers than those of married patients or those who have partners; lefthanders present better scores in social roles, even with the right hemisphere affected so as to cause n hemiplegia/hemiparesis. Comparing functional questions to the impact in the Quality of Life of those individuals, we can favor the improvement of interventions and treatments in Occupational Therapy for post-EVA patients.